Preferential enrichment and extraction of laser-synthesized nanoparticles in organic phases - Fromme, Theo; Spiekermann, Maximilian L.; Lehmann, Florian; Barcikowski, Stephan; Seidensticker, Thomas; Reichenberger, Sven (Beilstein Journal of Nanotechnology, 2025)
Pulsed laser ablation in liquids (LAL) is an established preparation method of nanoparticles and catalysts, which additionally allows to chemically modify the nanomaterials in situ via chemical reactions of the nanoparticles with the molecules or solutes of the liquid. Particularly when organic solvents are used as liquids, photothermally induced C–C cleavage, addition or dehydrogenation reactions of the solvents, as well as (carbon) functionalization of the nanoparticles have been observed, which ultimately should affect their lipophilicity and, hence, colloidal stability in apolar or polar solvents. Two-phase liquid systems and the possibility to transfer the surfactant-free nanoparticles from one liquid phase into another remain practically unaddressed in literature. To tackle this knowledge gap, the present study investigates the phase preference of laser-generated noble metal (Au and Ag) and base metal (Cu, Fe, Al and Ti) nanoparticles within propylene carbonate/alcohol (PC/A) systems. Alcohols of increasing chain length (C6–C11) and hence decreasing polarity were chosen for this study. For each metal, LAL was performed at elevated temperatures (85 °C) where the PC/A mixture forms a single phase. Upon cooling, the phases separated and the amount of colloidal nanoparticles in the alcohol and propylene carbonate phase was analyzed for each metal system. The abundance of nanoparticles in PC or alcohol was found to correlate with the electrochemical reduction potential of the respective metal, where the noble metals were enriched within the more polar solvents. The polarity of the solvents (as function of the carbon chain length of the alcohol) was found to direct both the nanoparticles’ phase selectivity and recovery after cycling. The observed correlations provide potential guidelines for nanoparticle extraction and size separation, relevant for phase transfer and cycling during homogeneous catalysis.
Keywords: catalysis; laser ablation in liquid; laser synthesis and processing of colloids; phase transfer; size separation; thermomorphic multiphase system